Biofeedback Modalities Targeting Kyphosis and Lordosis: A Critical Appraisal Topic. - Rajabi, Reza; Minoonejad, Hooman; Khorramroo, Fateme; Bafrouei, Mostafa Jalili; Banerjee, Baisakhi (BioMed Research International, 2026)
Background: Postural deviations such as thoracic kyphosis and lumbar lordosis are prevalent consequences of sedentary behavior, contributing to pain and disability. We aim to review the evidence on biofeedback modalities as active, user‐engaged alternatives to passive correction targeting kyphosis and lordosis posture. Methods: A systematic search of PubMed, Web of Science, Scopus, and IEEE Xplore (inception: September 2025) identified studies on adult populations. Primary outcomes were spinal alignment measures; secondary outcomes included muscle activity, pain, usability, and satisfaction. The results of the included studies were synthesized in a qualitative narrative way. Results: Fourteen studies involving 288 participants met inclusion criteria. Most studies used accelerometers or IMUs for posture detection. The most frequently applied modality was vibration feedback (n = 6), followed by auditory (n = 3), visual (n = 3), and multimodal systems (n = 2). Across studies, short‐term improvements were consistent: reduced kyphotic (up to 8°) and lordotic (up to 10°) angles, decreased pain, and improved trunk posture (p < 0.05); enhanced awareness and spinal muscle relaxation (p < 0.05); and actuator‐based systems achieved up to 25° of active correction but lacked long‐term data. Modalities showed usability and user satisfaction and had postural measurement error of 1°–4° across studies. Conclusion: Biofeedback modalities—particularly vibration and auditory systems—demonstrate measurable improvements in spinal alignment and engagement. Evidence is limited by low methodological rigor, small sample sizes, and short‐term focus. Future research should investigate the effectiveness of biofeedback in longitudinal, real‐world trials, with multimodal feedback and ergonomic integration for sustained postural correction.